Uso de grão de milho inteiro ou laminado como suplemento para bezerras de corte em pastejo em azevém - Oliveira, Ana Paula Binato Beltrão de (2012)
The performance of beef heifers grazing Italian ryegrass (Lolium multiflorum Lam) from eight until twelve months receiving or not energetic supplement (whole corn grain or steam-rolled) at level of 1% body weight were studied. The grazing method was continuous with variable number of animals. The suplement was given daily at 2 pm and presented 9,5% crude protein, 8,4% neutral detergent fiber and 83% total digestible nutrients. The experimental design was completely randomized with repeated measures on time and the sward and animals variable were studied. The beef heifers were submitted to average values of forage mass (1525,2 kg/ha of dry matter) and sward height (9,6 cm). There was no difference between the performance of beef heifers that receiving different physical forms of corn grain (P>0,05) and the average values of whole corn grain and steam-rolled corn was used. The beef heifers receiving corn grain had higher average daily gain, body condition score and body weight:height ratio than heifers exclusively on pasture. The use of corn grain as a supplement expressed no change in pelvic area and reproductive tract score of beef heifers. The supplementation with corn grain allows higher number of beef heifers grazing on ryegrass pasture and gain per area.